A composite-pore active biochar adsorbent for adsorptive separation of azeotrope and a preparation method and application thereof

CN122974273APending Publication Date: 2026-10-27CHANGZHOU UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611134336.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-29
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

酸改性是应用最广泛的化学改性方法之一,但这里的酸仅限于无机酸或路易斯酸,其作用目标单一,仅在于调控孔道结构,如提高中孔率、大孔率或实现孔径差异化,既未涉及使用有机酸对生物炭表面进行官能团接枝活化,也未针对甲醇-碳酸二甲酯共沸物这一特定分离体系进行表面化学性质的设计

Benefits of technology

[0028](1)传统酸改性只能进行孔道调控,无法表面化学活化。本发明通过无机酸造孔、有机酸接枝、 路易斯酸配位扩孔的串联改性,制备得到微孔-中大孔的复合孔道结构,不仅提高了吸附过程中的传质速率,还增加了表面活性位种类与数量,增大吸附容量,改善吸附剂对甲醇-碳酸二甲酯的分离性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122974273A_ABST
    Figure CN122974273A_ABST
Patent Text Reader

Abstract

The present application belongs to the technical field of adsorption separation materials, and particularly relates to a composite pore type active biochar adsorbent for adsorption separation of azeotrope, a preparation method and application thereof. The present application proposes a three-acid step-by-step preparation process. First, raw biomass powder is prepared by selecting biomass raw materials, and the first acid treatment is performed using inorganic acid, and then microporous biochar material is prepared through pyrolysis. Next, the microporous biochar is dispersed in an organic acid system for the second acid treatment and functional group activation to prepare microporous active biochar material. Finally, the third acid treatment is performed using Lewis acid, and after calcination, the composite pore type active biochar adsorbent is finally prepared. The preparation method controls the pore size, optimizes the pore type and enriches the surface active functional groups through the synergistic effect of three acids, and the obtained composite pore type active biochar adsorbent simultaneously satisfies the dual effects of large adsorption capacity and high separation selectivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of adsorption and separation materials technology, specifically relating to a composite porous biochar adsorbent for methanol-dimethyl carbonate azeotrope and its preparation method. Background Technology

[0002] Since DMC and its raw material methanol (MeOH) form an azeotrope, the technical challenge in producing battery-grade DMC lies in breaking this MeOH-DMC azeotropic system. To achieve the industrialization of MeOH-DMC adsorption and separation, the key is to prepare a high-performance adsorbent that combines adsorption capacity, separation selectivity, and stability.

[0003] Existing porous materials used for the adsorption and separation of methanol-dimethyl carbonate azeotropes include clay materials, zeolites, and molecular sieves. Patent CN114433008B discloses a method for preparing an attapulgite composite material for the adsorption and separation of methanol / dimethyl carbonate, wherein the dynamic saturated adsorption capacities of the obtained adsorbent for methanol and dimethyl carbonate are 288.12 mg·g⁻¹, respectively. -1 With 60.23 mg·g -1 The adsorption performance is relatively low. Meanwhile, clay materials, represented by attapulgite, have relatively fixed pore structures, narrow pore size distributions, and high surface chemical stability, making it difficult to flexibly control the pore structure and surface active groups through subsequent modification. Furthermore, some studies (adsorption and separation of dimethyl carbonate-methanol azeotrope) have used hydrophobic silica zeolite Si-1 and high-silica HZSM-5 molecular sieve adsorbents for the dynamic adsorption and separation of methanol-dimethyl carbonate gas-phase azeotrope. The results show that Si-1 achieves an adsorption selectivity of 86% and a separation factor of 14.77, but its saturated adsorption mass for dimethyl carbonate is only 3.48 g / 100g adsorbent (i.e., 34.8 mg·g⁻¹). -1 The adsorption capacity is significantly low. Furthermore, while this technology successfully separates methanol and dimethyl carbonate, the adsorbent cannot precisely capture methanol molecules. Therefore, the substance remaining in the gas phase after adsorption is high-purity methanol, not the high-quality dimethyl carbonate required for industrial applications. Meanwhile, the synthesis process of molecular sieve materials typically involves complex steps such as high-temperature crystallization, template agent use, and subsequent calcination to remove the template, resulting in a long preparation cycle, high cost, and the predominantly microporous structure of molecular sieves leading to slow mass transfer rates. Additionally, the regeneration conditions for molecular sieve materials are quite demanding, usually requiring high-temperature heat treatment to completely remove the adsorbate. After multiple regenerations, the framework structure is prone to dealuminization or collapse, leading to irreversible degradation of adsorption performance and difficulty in ensuring cycle stability. It is clear that the existing technologies for separating methanol-dimethyl carbonate azeotropes generally suffer from shortcomings such as low adsorption capacity, complex synthesis methods, low structural stability, difficulty in surface control, and weak directional capture of methanol molecules.

[0004] Activated carbon, as a traditional adsorbent, possesses advantages such as large specific surface area, high adsorption capacity, good stability, and low cost, and is widely used in the field of adsorption separation. Acid modification is one of the most widely used chemical modification methods, but the acids used here are limited to inorganic acids or Lewis acids, with a singular objective: to control the pore structure, such as increasing mesoporosity, macroporosity, or achieving pore size differentiation. It does not involve the use of organic acids to activate functional groups on the biochar surface, nor does it involve the design of surface chemical properties for the specific separation system of methanol-dimethyl carbonate azeotrope.

[0005] The present invention aims to address the problem that conventional modification methods cannot simultaneously achieve multiple objectives such as controlling pore size, optimizing pore shape, and enriching surface active functional groups, resulting in low adsorption mass transfer efficiency, insufficient separation selectivity, or weak ability to directionally capture methanol molecules in modified biochar for methanol-dimethyl carbonate azeotropes, which makes it difficult to meet the requirements for deep and efficient separation of this azeotropic system in the production of battery-grade dimethyl carbonate. Summary of the Invention

[0006] To address the problems in the background art, this invention provides a composite porous biochar adsorbent and its preparation method. This invention uses agricultural and forestry waste as biochar raw material, and employs a stepwise modification method involving inorganic acid, organic acid, and Lewis acid to regulate pore size, optimize pore type, and enrich surface active functional groups, ultimately meeting the requirements of biochar adsorbent materials in terms of adsorption capacity and separation selectivity.

[0007] The preparation method of composite porous activated biochar adsorbent includes the following steps:

[0008] (1) Preparation of raw biomass powder: The biomass raw material is crushed by a crusher, then washed with deionized water, dried in air at 70-90℃, ground and passed through an 80-120 mesh standard sieve to obtain raw biomass powder;

[0009] (2) Preparation of microporous biochar material: The original biomass powder obtained in step (1) is dispersed in an inorganic acid solution with a mass concentration of 5-15%, stirred at 110-120℃ for 1-2h, separated, washed until the pH of the filtrate is neutral, vacuum dried at 70-90℃ for 4-6h, and then pyrolyzed in a nitrogen atmosphere at 550℃-650℃ for 3-4h to obtain microporous biochar material;

[0010] (3) Preparation of microporous activated biochar material: Disperse the microporous biochar material obtained in step (2) in an organic acid solution with a mass concentration of 2-10%, stir at 60-70℃ for 1-2 hours, separate, wash the filter cake until the pH of the filtrate is neutral, and vacuum dry the filter cake at 70-90℃ for 4-6 hours to obtain microporous activated biochar material;

[0011] (4) Preparation of composite porous activated biochar adsorbent: The microporous activated biochar material obtained in step (3) is immersed in a Lewis acid solution with a concentration of 0.25-1.00 mol / L, stirred at room temperature for 1-2 h, filtered, dried in air at 70-90℃ for 4-6 h, calcined in air at 250-350℃ for 1-2 h, and passed through an 80-120 mesh standard sieve to obtain the composite porous activated biochar adsorbent.

[0012] Preferably, the biomass raw material is agricultural waste such as straw, corn cob, sugarcane bagasse, coconut shell, and orange peel.

[0013] Preferably, the inorganic acid is at least one selected from phosphoric acid, sulfuric acid, nitric acid, and hydrochloric acid.

[0014] Preferably, the organic acid is at least one selected from acetic acid, oxalic acid, citric acid, and malic acid.

[0015] Preferably, the Lewis acid is at least one of AlCl3, ZnCl2, and FeCl3.

[0016] Preferably, the mass concentration of the inorganic acid solution in step (2) is 8-12%.

[0017] Preferably, in step (2), the ratio of raw biomass powder to inorganic acid solution is 10-12g:120-200mL.

[0018] Preferably, the concentration of the organic acid solution in step (3) is 3-8%.

[0019] Preferably, in step (3), the ratio of microporous biochar material to organic acid solution is 9-11g:60-80mL.

[0020] Preferably, the concentration of the Lewis acid solution in step (4) is 0.30-0.8 mol / L.

[0021] Preferably, in step (4), the ratio of microporous activated biochar material to Lewis acid solution is 8-11g:35-45mL.

[0022] A composite porous activated biochar adsorbent prepared by the above method.

[0023] The composite porous activated biochar adsorbent prepared by the above method is used for the separation of methanol-dimethyl carbonate azeotrope.

[0024] The above-mentioned composite porous activated biochar adsorbent was applied to the separation of methanol-dimethyl carbonate azeotrope, and the specific steps are as follows:

[0025] The composite porous activated biochar adsorbent was mixed with a methanol-dimethyl carbonate azeotropic solution, placed in an Erlenmeyer flask, and then placed in a constant temperature shaker for azeotropic adsorption and separation.

[0026] Preferably, the mass ratio of methanol:dimethyl carbonate:N,N-dimethylformamide in the methanol-dimethyl carbonate azeotropic solution is (14~56):(6~24):(20~80).

[0027] Compared with the prior art, the present invention has the following advantages:

[0028] (1) Traditional acid modification can only regulate pores and cannot activate the surface chemically. This invention prepares a composite pore structure of micropores and mesopores by tandem modification of inorganic acid pore formation, organic acid grafting, and Lewis acid coordination expansion. This not only improves the mass transfer rate during adsorption but also increases the types and number of surface active sites, increases the adsorption capacity, and improves the separation performance of the adsorbent for methanol-dimethyl carbonate.

[0029] (2) Compared with the traditional acid treatment method of activated carbon, the present invention breaks through the limitation of single acid treatment and achieves multiple objectives of controlling pore size, optimizing pore shape and enriching surface active functional groups, thereby greatly improving the adsorption capacity and separation selectivity of adsorbent for methanol-dimethyl carbonate azeotrope. Attached Figure Description

[0030] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly described below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation of the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.

[0031] Figure 1 This is a scanning electron microscope image of the composite porous activated biochar of Example 1.

[0032] Figure 2 The nitrogen adsorption-desorption curves for the composite porous activated biochar in Example 1 are shown.

[0033] Figure 3 The bar chart shows the static saturated adsorption capacity of the methanol-dimethyl carbonate azeotrope on the composite porous activated biochar treated with different inorganic acids in Examples 1-4.

[0034] Figure 4 For Examples 1, 5-7, the static saturated adsorption capacity of composite porous activated biochar treated with different concentrations of phosphoric acid for methanol-dimethyl carbonate azeotrope is shown in the bar chart.

[0035] Figure 5 For Example 1, 8-10, the static saturated adsorption capacity of the composite porous activated biochar activated with different organic acids for methanol-dimethyl carbonate azeotrope is shown in the bar chart.

[0036] Figure 6 For Example 1, 11-13, the static saturated adsorption capacity of the composite porous activated biochar activated with different concentrations of acetic acid on the methanol-dimethyl carbonate azeotrope is shown in the bar chart.

[0037] Figure 7 For Example 1, 14-15 are bar charts showing the static saturated adsorption capacity of methanol-dimethyl carbonate on composite porous activated biochar after pore expansion with different Lewis acids.

[0038] Figure 8 For Example 1, 16-17 are bar charts showing the static saturated adsorption capacity of the composite porous activated biochar after pore expansion with AlCl3 solution of different concentrations on methanol-dimethyl carbonate solution. Detailed Implementation

[0039] To further understand the purpose, content, and advantages of this invention, specific embodiments of the invention are described in detail below. However, these embodiments are not limited to the examples described below and should be freely combined according to actual circumstances. The endpoints and values ​​of the ranges disclosed herein are not limited to the precise ranges and values. For numerical ranges, endpoint values ​​of various ranges, endpoint values ​​of various ranges and individual point values, and individual point values ​​can be combined to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0040] The biomass raw materials used in the following embodiments of the present invention are agricultural wastes such as straw, corn cobs, sugarcane bagasse, coconut shells, and orange peels.

[0041] The phosphoric acid used in the following embodiments of the present invention was of analytical grade and purchased from Sinopharm Chemical Reagent Co., Ltd.

[0042] The hydrochloric acid used in the following embodiments of the present invention was of analytical grade and purchased from Sinopharm Chemical Reagent Co., Ltd.

[0043] The sulfuric acid used in the following embodiments of the present invention was of analytical grade and purchased from Sinopharm Chemical Reagent Co., Ltd.

[0044] The nitric acid used in the following examples of the present invention was of analytical grade and purchased from Sinopharm Chemical Reagent Co., Ltd.

[0045] The acetic acid used in the following examples of the present invention was of analytical grade and purchased from Sinopharm Chemical Reagent Co., Ltd.

[0046] The oxalic acid used in the following examples of the present invention was of analytical grade and purchased from Sinopharm Chemical Reagent Co., Ltd.

[0047] The citric acid used in the following examples of the present invention was of analytical grade and purchased from Sinopharm Chemical Reagent Co., Ltd.

[0048] The malic acid used in the following examples of the present invention was of analytical grade and purchased from Sinopharm Chemical Reagent Co., Ltd.

[0049] The anhydrous AlCl3 used in the following examples of the present invention was of analytical grade and purchased from Sinopharm Chemical Reagent Co., Ltd.

[0050] The anhydrous FeCl3 used in the following examples of the present invention was of analytical grade and purchased from Sinopharm Chemical Reagent Co., Ltd.

[0051] The anhydrous ZnCl2 used in the following examples of the present invention was of analytical grade and purchased from Sinopharm Chemical Reagent Co., Ltd.

[0052] The nitrogen gas used in the following embodiments of the present invention is analytical grade with a purity of 99.99%.

[0053] However, this patent does not restrict the source of biomass raw materials, phosphoric acid, hydrochloric acid, sulfuric acid, nitric acid, acetic acid, oxalic acid, citric acid, malic acid, AlCl3, ZnCl2, FeCl3, and nitrogen, etc. Anything that can be purchased on the market is applicable to the method of this patent.

[0054] This invention provides a method for preparing composite porous activated biochar, comprising the following steps:

[0055] (1) Preparation of raw biomass powder: The biomass raw material is crushed by a crusher, then washed with deionized water, dried in air at 70-90℃, ground and passed through an 80-120 mesh standard sieve to obtain raw biomass powder;

[0056] (2) Preparation of microporous biochar material: The original biomass powder obtained in step (1) is dispersed in an inorganic acid solution with a mass concentration of 5-15%, stirred at 110-120℃ for 1-2h, filtered and washed until the pH of the filtrate is neutral, vacuum dried at 70-90℃ for 4-6h, and then pyrolyzed in a nitrogen atmosphere at 550℃-650℃ for 3-4h to obtain microporous biochar material;

[0057] (3) Preparation of microporous activated biochar material: Disperse the microporous biochar material obtained in step (2) in an organic acid solution with a mass concentration of 2-10%, stir at 60-70℃ for 1-2 hours, filter and wash until the pH of the filtrate is neutral, and vacuum dry at 70-90℃ for 4-6 hours to obtain microporous activated biochar material.

[0058] (4) Preparation of composite porous activated biochar adsorbent: The microporous activated biochar material obtained in step (3) is immersed in a Lewis acid solution with a concentration of 0.25-1.00 mol / L, stirred at room temperature for 1-2 h, filtered, dried in air at 70-90℃ for 4-6 h, calcined in air at 250-350℃ for 1-2 h, and passed through an 80-120 mesh standard sieve to obtain the composite porous activated biochar adsorbent.

[0059] The types of inorganic acids, the concentrations and types of organic acids, and the concentrations and types of Lewis acids in the preparation method are key parameters affecting the adsorption and separation performance of the composite porous activated biochar on methanol-dimethyl carbonate azeotrope. Other factors are non-critical and will not have a significant impact on product performance as long as they are controlled within the specified range (the impact can be ignored).

[0060] More specific examples are as follows:

[0061] Example 1

[0062] (1) Preparation of raw biomass powder: Coconut shells are selected as biomass raw materials, crushed by a crusher, washed with deionized water, dried in air at 80°C for 6 hours, ground and passed through an 80-120 mesh standard sieve to obtain raw biomass powder.

[0063] (2) Preparation of microporous biochar material: Weigh 12g of raw biomass powder, disperse it in 150mL of 10% phosphoric acid solution, stir at 110℃ for 1h, filter and wash until the pH of the filtrate is neutral, vacuum dry at 80℃ for 4h, and then pyrolyze in a nitrogen atmosphere at 600℃ for 3h to obtain microporous biochar material.

[0064] (3) Preparation of microporous activated biochar material: 10g of microporous biochar material was dispersed in 70mL of 5% acetic acid solution, stirred at 60℃ for 1h, filtered and washed until the pH of the filtrate was neutral, and then vacuum dried at 90℃ for 4h to obtain microporous activated biochar material.

[0065] (4) Preparation of composite porous activated biochar adsorbent: 9g of microporous activated biochar material was immersed in 40mL of AlCl3 solution with a concentration of 0.5mol / L, stirred at room temperature for 1h, filtered, dried in air at 80℃ for 4h, calcined in air at 300℃ for 1h, and passed through an 80-120 mesh standard sieve to finally obtain composite porous activated biochar adsorbent.

[0066] Static adsorption experiments were conducted using N,N-dimethylformamide (DMF) as an inert solvent to prepare an azeotropic simulation solution with a methanol:dimethyl carbonate:DMF mass ratio of 35:15:50. 1.0 g of composite porous activated biochar adsorbent was weighed and mixed with 20 mL of the azeotropic simulation solution. The mixture was placed in an Erlenmeyer flask and placed in a constant-temperature shaking bed at 25 °C for azeotropic adsorption separation. Shaking was continued for 4 h until adsorption equilibrium was reached. After standing, the supernatant was collected, and the concentration of the adsorbed solution was determined using gas chromatography. The calculated saturated adsorption capacity for methanol was 1941.64 mg / g, the saturated adsorption capacity for dimethyl carbonate was 468.77 mg / g, and the selectivity was 4.14.

[0067] Figure 1 The image shown is a scanning electron microscope (SEM) image of the composite porous activated biochar adsorbent prepared in Example 1 of this invention. The adsorbent exhibits a honeycomb porous structure with interconnected channels and intact, uniform pore walls, showing no obvious collapse or blockage. Macropores and mesopores are clearly visible, forming a composite pore system with a micropore-mesopore-macropore hierarchical distribution together with the micropore structure. Simultaneously, the rough, wrinkled pore wall surface provides ample chemisorption sites for methanol molecules. This composite porous structure facilitates rapid diffusion and mass transfer of adsorbate molecules within the pores, and enhances the adsorbent's specific recognition ability for methanol through abundant surface active sites.

[0068] Figure 2 The nitrogen adsorption-desorption isotherm of Example 1 shows typical Type IV characteristics, with a distinct H3-type hysteresis loop appearing in the medium-high pressure region, proving the existence of abundant mesoporous structures in the material, consistent with the pore volume data in Table 1. Figure 1 The electron microscopy results are consistent.

[0069] Example 2

[0070] The difference from Example 1 is that when preparing the composite porous activated biochar adsorbent, the inorganic acid used in step (2) is hydrochloric acid, and the rest of the operation is the same as in Example 1.

[0071] After the static experiment, the saturated adsorption capacity of the composite porous activated biochar adsorbent for methanol was 1635.14 mg / g, the saturated adsorption capacity for dimethyl carbonate was 427.41 mg / g, and the selectivity was 3.83.

[0072] Example 3

[0073] The difference from Example 1 is that when preparing the composite porous activated biochar adsorbent, the inorganic acid used in step (2) is sulfuric acid, and the rest of the operation is the same as in Example 1.

[0074] After the static experiment, the saturated adsorption capacity of the composite porous activated biochar adsorbent for methanol was 1298.51 mg / g, the saturated adsorption capacity for dimethyl carbonate was 398.54 mg / g, and the selectivity was 3.26.

[0075] Example 4

[0076] The difference from Example 1 is that when preparing the composite porous activated biochar adsorbent, the inorganic acid used in step (2) is nitric acid, and the rest of the operation is the same as in Example 1.

[0077] After the static experiment, the saturated adsorption capacity of the composite porous activated biochar adsorbent for methanol was 1389.69 mg / g, the saturated adsorption capacity for dimethyl carbonate was 451.54 mg / g, and the selectivity was 3.08.

[0078] Figure 3 To investigate the effects of different inorganic acids on adsorption performance, the methanol saturation adsorption capacity and selectivity of the adsorbent obtained by the first acid treatment with phosphoric acid were superior to those obtained by treatment with hydrochloric acid, sulfuric acid, or nitric acid. This is because phosphoric acid has moderate acidity and good wetting and etching capabilities, which can effectively open up the biomass fiber structure and obtain a uniform microporous framework, providing an ideal substrate for subsequent grafting of organic acid functional groups and pore expansion with Lewis acids.

[0079] Example 5

[0080] The difference from Example 1 is that when preparing the composite porous activated biochar adsorbent, the phosphoric acid solution used in step (2) has a mass fraction of 5%, and the rest of the operation is the same as in Example 1.

[0081] After the static experiment, the saturated adsorption capacity of the composite porous activated biochar adsorbent for methanol was 1549.14 mg / g, the saturated adsorption capacity for dimethyl carbonate was 402.47 mg / g, and the selectivity was 3.85.

[0082] Example 6

[0083] The difference from Example 1 is that when preparing the composite porous activated biochar adsorbent, the phosphoric acid solution used in step (2) has a mass fraction of 8%, and the rest of the operation is the same as in Example 1.

[0084] After the static experiment, the saturated adsorption capacity of the composite porous activated biochar adsorbent for methanol was 1675.38 mg / g, the saturated adsorption capacity for dimethyl carbonate was 411.52 mg / g, and the selectivity was 4.07.

[0085] Example 7

[0086] The difference from Example 1 is that when preparing the composite porous activated biochar adsorbent, the phosphoric acid solution used in step (2) has a mass fraction of 15%, and the rest of the operation is the same as in Example 1.

[0087] After the static experiment, the saturated adsorption capacity of the composite porous activated biochar adsorbent for methanol was 1765.38 mg / g, the saturated adsorption capacity for dimethyl carbonate was 473.67 mg / g, and the selectivity was 3.73.

[0088] Figure 4 To investigate the effect of phosphoric acid concentration on adsorption performance, as the phosphoric acid concentration increased from 5% to 10%, both the methanol saturation adsorption capacity and selectivity of the adsorbent continuously improved, reaching their optimal values ​​at a phosphoric acid concentration of 10%. Further increasing the concentration to 15%, while the methanol adsorption capacity remained at a high level, the selectivity decreased. This indicates that excessively low phosphoric acid concentrations result in insufficient pore formation, failing to provide a sufficient microporous substrate for subsequent functional group grafting; while excessively high concentrations lead to over-etching of the biomass fiber structure, damaging the pore integrity and negatively impacting selectivity.

[0089] Example 8

[0090] The difference from Example 1 is that when preparing the composite porous activated biochar adsorbent, the organic acid used in step (3) is oxalic acid, and the rest of the operation is the same as in Example 1.

[0091] After the static experiment, the saturated adsorption capacity of the composite porous activated biochar adsorbent for methanol was 1357.46 mg / g, the saturated adsorption capacity for dimethyl carbonate was 462.96 mg / g, and the selectivity was 2.93.

[0092] Example 9

[0093] The difference from Example 1 is that when preparing the composite porous activated biochar adsorbent, the organic acid used in step (3) is citric acid, and the rest of the operation is the same as in Example 1.

[0094] After the static experiment, the saturated adsorption capacity of the composite porous activated biochar adsorbent for methanol was 1531.41 mg / g, the saturated adsorption capacity for dimethyl carbonate was 497.67 mg / g, and the selectivity was 3.08.

[0095] Example 10

[0096] The difference from Example 1 is that when preparing the composite porous activated biochar adsorbent, the organic acid used in step (3) is malic acid, and the rest of the operation is the same as in Example 1.

[0097] After the static experiment, the saturated adsorption capacity of the composite porous activated biochar adsorbent for methanol was 1279.86 mg / g, the saturated adsorption capacity for dimethyl carbonate was 397.85 mg / g, and the selectivity was 3.22.

[0098] Figure 5 To investigate the effects of different organic acids on adsorption performance, the second acid treatment with acetic acid resulted in adsorbents with significantly higher methanol saturation adsorption capacity and selectivity compared to treatments with oxalic acid, citric acid, or malic acid. This is because acetic acid, with its suitable acidity and small molecular size, can effectively penetrate the micropores to graft functional groups, introducing a large number of oxygen-containing active groups such as carboxyl and hydroxyl groups. This, in turn, enhances the adsorption capacity while endowing the material with excellent selective recognition capabilities.

[0099] Example 11

[0100] The difference from Example 1 is that when preparing the composite porous activated biochar adsorbent, the acetic acid solution used in step (3) has a mass fraction of 2%, and the rest of the operation is the same as in Example 1.

[0101] After the static experiment, the saturated adsorption capacity of the composite porous activated biochar adsorbent for methanol was 1481.34 mg / g, the saturated adsorption capacity for dimethyl carbonate was 491.41 mg / g, and the selectivity was 3.01.

[0102] Example 12

[0103] The difference from Example 1 is that when preparing the composite porous activated biochar adsorbent, the acetic acid solution used in step (3) has a mass fraction of 7%, and the rest of the operation is the same as in Example 1.

[0104] After the static experiment, the saturated adsorption capacity of the composite porous activated biochar adsorbent for methanol was 1575.32 mg / g, the saturated adsorption capacity for dimethyl carbonate was 451.78 mg / g, and the selectivity was 3.49.

[0105] Example 13

[0106] The difference from Example 1 is that when preparing the composite porous activated biochar adsorbent, the acetic acid solution used in step (3) has a mass fraction of 10%, and the rest of the operation is the same as in Example 1.

[0107] After the static experiment, the saturated adsorption capacity of the composite porous activated biochar adsorbent for methanol was 1641.42 mg / g, the saturated adsorption capacity for dimethyl carbonate was 471.53 mg / g, and the selectivity was 3.48.

[0108] Figure 6 To investigate the effect of different acetic acid concentrations on adsorption performance, as the acetic acid concentration increased from 2% to 5%, both the methanol adsorption capacity and selectivity of the adsorbent improved, reaching an optimal level at 5%. Further increases in concentration to 7% and 10% resulted in a slight increase in methanol adsorption capacity, but a decrease in selectivity. This is because excessively low acetic acid concentrations lead to insufficient functional group grafting and an insufficient number of active sites, failing to effectively improve adsorption selectivity; while excessively high concentrations may cause excessive corrosion of the pore structure, which is detrimental to further improvement in selectivity.

[0109] Example 14

[0110] The difference from Example 1 is that when preparing the composite porous activated biochar adsorbent, the Lewis acid used in step (4) is ZnCl2, and the rest of the operation is the same as in Example 1.

[0111] After the static experiment, the saturated adsorption capacity of the composite porous activated biochar adsorbent for methanol was 1475.24 mg / g, the saturated adsorption capacity for dimethyl carbonate was 402.41 mg / g, and the selectivity was 3.67.

[0112] Example 15

[0113] The difference from Example 1 is that when preparing the composite porous activated biochar adsorbent, the Lewis acid used in step (4) is FeCl3, and the rest of the operation is the same as in Example 1.

[0114] After the static experiment, the saturated adsorption capacity of the composite porous activated biochar adsorbent for methanol was 1151.31 mg / g, the saturated adsorption capacity for dimethyl carbonate was 386.39 mg / g, and the selectivity was 2.98.

[0115] Figure 7 To investigate the effects of different Lewis acids on adsorption performance, the methanol saturation adsorption capacity and selectivity of the adsorbent obtained by the third acid treatment with aluminum chloride were better than those obtained by the treatment with zinc chloride or ferric chloride.

[0116] Example 16

[0117] The difference from Example 1 is that when preparing the composite porous activated biochar adsorbent, the concentration of AlCl3 solution used in step (4) is 0.25 mol / L, and the rest of the operation is the same as in Example 1.

[0118] After the static experiment, the saturated adsorption capacity of the composite porous activated biochar adsorbent for methanol was 1615.24 mg / g, the saturated adsorption capacity for dimethyl carbonate was 534.25 mg / g, and the selectivity was 3.02.

[0119] Example 17

[0120] The difference from Example 1 is that when preparing the composite porous activated biochar adsorbent, the concentration of AlCl3 solution used in step (4) is 1.0 mol / L, and the rest of the operation is the same as in Example 1.

[0121] After the static experiment, the saturated adsorption capacity of the composite porous activated biochar adsorbent for methanol was 1702.51 mg / g, the saturated adsorption capacity for dimethyl carbonate was 496.75 mg / g, and the selectivity was 3.43.

[0122] Figure 8 To investigate the effect of different aluminum chloride concentrations on adsorption performance, as the aluminum chloride concentration increased from 0.25 mol / L to 0.5 mol / L, both the methanol adsorption capacity and selectivity of the adsorbent improved, reaching the optimal value at 0.5 mol / L; when the concentration was further increased to 1.0 mol / L, both the methanol adsorption capacity and selectivity decreased.

[0123] Comparative Example 1

[0124] Similar to Example 1, except that after preparing the microporous activated biochar material, without the Lewis acid pore-expanding treatment in step (4), the microporous activated biochar material prepared in step (3) was directly calcined in an air atmosphere at 300°C, and the rest of the operation was the same as in Example 1.

[0125] After the static experiment, the saturated adsorption capacity of the composite porous activated biochar adsorbent for methanol was 987.14 mg / g, the saturated adsorption capacity for dimethyl carbonate was 471.71 mg / g, and the selectivity was 2.09.

[0126] Comparative Example 2

[0127] Same as Example 1, except that when preparing the composite porous activated biochar adsorbent, the organic acid activation treatment in step (3) was not used, and the rest of the operation was the same as in Example 1.

[0128] After the static experiment, the saturated adsorption capacity of the composite porous activated biochar adsorbent for methanol was 1158.70 mg / g, the saturated adsorption capacity for dimethyl carbonate was 439.58 mg / g, and the selectivity was 2.64.

[0129] Comparative Example 3

[0130] Similar to Example 1, the difference is that when preparing microporous biochar material, the original biomass powder was not treated with inorganic acid in step (2) for microporous treatment. Instead, the original biomass powder was directly pyrolyzed at 600°C in a nitrogen atmosphere, and then treated in steps (3)-(4). The remaining operations were the same as in Example 1.

[0131] After the static experiment, the saturated adsorption capacity of the composite porous activated biochar adsorbent for methanol was 809.41 mg / g, the saturated adsorption capacity for dimethyl carbonate was 387.73 mg / g, and the selectivity was 2.09.

[0132] Comparative Example 4

[0133] Similar to Example 1, except that after preparing the microporous biochar material, the organic acid in step (3) was not used for activation treatment, nor was the Lewis acid in step (4) used for pore expansion treatment. Instead, the microporous biochar material prepared in step (2) was directly calcined in an air atmosphere at 300°C. The remaining operations were the same as in Example 1.

[0134] After the static experiment, the saturated adsorption capacity of the composite porous activated biochar adsorbent for methanol was 879.41 mg / g, the saturated adsorption capacity for dimethyl carbonate was 401.61 mg / g, and the selectivity was 2.19.

[0135] Comparative Example 5

[0136] Similar to Example 1, the difference lies in that when preparing the composite porous activated biochar adsorbent, the original biomass powder was not treated with inorganic acid in step (2), but was directly pyrolyzed in a nitrogen atmosphere at 600°C for 3 hours. Subsequently, it was treated with organic acid in step (3) but not with Lewis acid. After organic acid treatment, the biochar material was calcined in an air atmosphere at 300°C. The remaining operations were the same as in Example 1.

[0137] After the static experiment, the saturated adsorption capacity of the composite porous activated biochar adsorbent for methanol was 705.12 mg / g, the saturated adsorption capacity for dimethyl carbonate was 385.15 mg / g, and the selectivity was 1.83.

[0138] Comparative Example 6

[0139] Same as Example 1, except that: when preparing the composite porous activated biochar adsorbent, the original biomass powder was treated with inorganic acid and then directly pyrolyzed in a nitrogen atmosphere at 600°C for 3 hours. The subsequent activation treatment with organic acid in step (3) was not used; instead, the biochar was treated with Lewis acid in step (4) and then calcined in an air atmosphere at 300°C. The remaining operations were the same as in Example 1.

[0140] After the static experiment, the saturated adsorption capacity of the composite porous activated biochar adsorbent for methanol was 721.42 mg / g, the saturated adsorption capacity for dimethyl carbonate was 395.26 mg / g, and the selectivity was 1.82.

[0141] Comparative Example 7

[0142] Same as Example 1, except that: when preparing the composite porous activated biochar adsorbent, it is first activated with an organic acid, then microporous with an inorganic acid, and finally expanded with a Lewis acid. The remaining operations are the same as in Example 1.

[0143] The specific steps are as follows:

[0144] 12g of raw biomass powder was dispersed in 70mL of 5% acetic acid solution, stirred at 60℃ for 1h, filtered and washed until the pH of the filtrate was neutral, and then vacuum dried at 90℃ for 4h.

[0145] The dried powder was dispersed in 150 mL of a 10% phosphoric acid solution and stirred at 110 °C for 1 h. After filtration, the powder was washed until the pH of the filtrate was neutral. After vacuum drying at 80 °C for 4 h, the powder was pyrolyzed at 600 °C in a nitrogen atmosphere for 3 h to obtain microporous biochar material.

[0146] 9g of microporous biochar material was impregnated in 40mL of 0.5mol / L AlCl3 solution, stirred at room temperature for 1h, filtered, dried in air at 80℃ for 4h, calcined in air at 300℃ for 1h, and passed through an 80-120 mesh standard sieve to obtain the adsorbent.

[0147] After the static experiment, the saturated adsorption capacity of the composite porous activated biochar adsorbent for methanol was 1121.82 mg / g, the saturated adsorption capacity for dimethyl carbonate was 378.67 mg / g, and the selectivity was 2.96.

[0148] Comparative Example 8

[0149] Same as Example 1, except that: when preparing the composite porous activated biochar adsorbent, it is first activated with an organic acid, then treated with a Lewis acid, and finally treated with an inorganic acid. The remaining operations are the same as in Example 1.

[0150] 12g of raw biomass powder was first dispersed in 70mL of 5% acetic acid solution, stirred at 60℃ for 1h, filtered and washed until the pH of the filtrate was neutral, and then vacuum dried at 90℃ for 4h.

[0151] The dried powder was immersed in 40 mL of 0.5 mol / L AlCl3 solution, stirred at room temperature for 1 h, filtered, dried in air at 80 °C for 4 h, and then calcined in air at 300 °C for 1 h.

[0152] The calcined powder was dispersed in 150 mL of a 10% phosphoric acid solution and stirred at 110 °C for 1 h. After filtration, the powder was washed until the pH of the filtrate was neutral. After vacuum drying at 80 °C for 4 h, the powder was pyrolyzed at 600 °C in a nitrogen atmosphere for 3 h, ground, and sieved to obtain the adsorbent.

[0153] After the static experiment, the saturated adsorption capacity of the composite porous activated biochar adsorbent for methanol was 1214.53 mg / g, the saturated adsorption capacity for dimethyl carbonate was 432.16 mg / g, and the selectivity was 2.81.

[0154] Comparative Example 9

[0155] 12g of raw biomass powder was weighed and dispersed in a mixed solution containing 10% phosphoric acid, 5% acetic acid, and 0.5mol / L AlCl3, with a total volume of 150mL. The solution was stirred and impregnated at 110℃ for 1h, followed by vacuum drying at 80℃ for 4h. The dried material was then placed in a tube furnace and pyrolyzed at 600℃ in a nitrogen atmosphere for 3h. After cooling, the pyrolysis product was washed with deionized water until the pH of the filtrate was neutral, and then dried again at 80℃. Finally, it was calcined at 300℃ in air for 1h, dried, and passed through an 80-120 mesh standard sieve to obtain the composite porous activated biochar adsorbent.

[0156] After the static experiment, the saturated adsorption capacity of the composite porous activated biochar adsorbent for methanol was 643.38 mg / g, the saturated adsorption capacity for dimethyl carbonate was 347.95 mg / g, and the selectivity was 1.85.

[0157] As can be seen from the above comparative examples, when any acid treatment step in the three-acid tandem process is omitted, the methanol adsorption capacity and selectivity of the resulting adsorbent are lower than those in Example 1. This indicates that inorganic acid, organic acid, and Lewis acid are all indispensable. Furthermore, the order of the three acid treatments cannot be changed; reversing this order will result in structural damage. The three acids cannot be mixed together for treatment, otherwise competitive etching will occur, leading to a homogenization of the pore structure, which will greatly affect the adsorption rate and dynamic adsorption efficiency.

[0158] Table 1. BET characterization results of Example 1 of the present invention

[0159]

[0160] Table 2. Parameter control of Examples 1 to 17 of the present invention and Comparative Examples 1 to 9.

[0161]

[0162] Table 3. Static adsorption and separation performance of the adsorbents prepared in Examples 1 to 17 and Comparative Examples 1 to 9 of the present invention on azeotropic simulated solutions.

[0163]

[0164] Based on the above-described preferred embodiments of the present invention, and through the foregoing description, those skilled in the art can make various changes and modifications without departing from the scope of the present invention. The technical scope of this invention is not limited to the contents of the specification, but must be determined according to the scope of the claims.

Claims

1. A method for preparing a composite porous activated biochar adsorbent, characterized in that, The preparation method includes the following steps: (1) Preparation of raw biomass powder: The biomass raw material is crushed by a crusher, washed with deionized water, dried, ground and sieved to obtain raw biomass powder; (2) Preparation of microporous biochar material: The original biochar powder obtained in step (1) is dispersed in an inorganic acid solution with a mass concentration of 5-15%, stirred at 110℃-120℃ for a period of time, separated and washed until neutral, and the filter cake is dried and then pyrolyzed in a nitrogen atmosphere at 550-650℃ for 3-4 hours to obtain microporous biochar material. (3) Preparation of microporous activated biochar material: The microporous biochar material obtained in step (2) is dispersed in an organic acid solution with a mass concentration of 2-10%, stirred at 60-70℃ for a period of time, separated, washed, and dried to obtain microporous activated biochar material; (4) Preparation of composite porous activated biochar adsorbent: The microporous activated biochar material obtained in step (3) is immersed in a Lewis acid solution with a concentration of 0.25-1.00 mol / L, stirred at room temperature and separated, dried in air at 70-90℃, and then calcined in air at 250-350℃ for 1-2 hours. After sieving, the composite porous activated biochar adsorbent is obtained.

2. The preparation method of the composite porous activated biochar adsorbent according to claim 1, characterized in that, The inorganic acid mentioned in step (2) is at least one of phosphoric acid, sulfuric acid, nitric acid or hydrochloric acid; the ratio of the amount of raw biochar powder to inorganic acid solution mentioned in step (2) is 10-12g:120-200mL.

3. The method for preparing the composite porous activated biochar adsorbent according to claim 1, characterized in that, The organic acid mentioned in step (3) is at least one of acetic acid, oxalic acid, citric acid or malic acid; The ratio of the microporous biochar material to the organic acid solution is 9-11g:60-80mL.

4. The method for preparing the composite porous activated biochar adsorbent according to claim 1, characterized in that, The Lewis acid solution mentioned in step (4) includes at least one of AlCl3, ZnCl2, and FeCl3; the ratio of the amount of microporous biochar activated biochar material to Lewis acid solution is 8-11g:35-45mL.

5. A composite porous activated biochar adsorbent prepared by the method according to any one of claims 1-4.

6. The application of the composite porous activated biochar adsorbent according to claim 5 in the separation of methanol-dimethyl carbonate azeotrope.

Citation Information

Patent Citations

  • Preparation method of attapulgite composite material for adsorption and separation of methanol / dimethyl carbonate

    CN114433008B